Cytotoxicity of bismuth(iii) dithiocarbamate derivatives by promoting a mitochondrial-dependent apoptotic pathway and suppressing MCF-7 breast adenocarcinoma cell invasion - Chan, Pit Foong; Ang, Kok Pian; Abd Hamid, Roslida (Springer, 2024)
We previously reported that the bismuth(III) dithiocarbamate derivative, bismuth diethyldithiocarbamate (1) exhibited greater cytotoxicity while inducing apoptosis via the intrinsic pathway in MCF-7 cells. We further evaluated the other bismuth(III) dithiocarbamate derivatives, BiS2CNR3, with R = (CH2CH2OH)(iPr), (CH2)4, and (CH2CH2OH)(CH3), denoted as 2, 3, and 4, respectively, in the same MCF-7 cell line. 2–4 were found to exhibit IC50 values of 10.33 ± 0.06 µM, 1.07 ± 0.01 µM and 25.37 ± 0.12 µM, respectively, compared to that of cisplatin at 30.53 ± 0.23 µM. Apoptotic promotion via the mitochondrial-dependent pathway was due to the elevation of intracellular reactive oxygen species (ROS), promotion of caspases, release of cytochrome c, fragmentation of DNA, and results of staining assay observed in all compound-treated cells. 2–4 are also capable of suppressing MCF-7 cell invasion and modulate Lys-48 also Lys-63 linked polyubiquitination, leading to proteasomal degradation. Analysis of gene expression via qRT-PCR revealed their modulation, which supported all activities conducted upon treatment with 2–4. Altogether, bismuth dithiocarbamate derivatives, with bismuth(III) as the metal center bound to ligands, isopropyl ethanol, pyrrolidine, and methyl ethanol dithiocarbamate, are potential anti-breast cancer agents that induce apoptosis and suppress metastasis. Further studies using other breast cancer cell lines and in vivo studies are recommended to clarify the anticancer effects of these compounds.